Supportive Care: An Indispensable Component of Modern Oncology. Issue 11 (November 2020) - Berman, R.; Davies, A.; Cooksley, T.; Gralla, R.; Carter, L.; Darlington, E.; Scotté, F.; Higham, C.
Abstract: The advent of new cancer therapies, alongside expected growth and ageing of the population, better survival rates and associated costs of care, is uncovering a need to more clearly define and integrate supportive care services across the whole spectrum of the disease. The current focus of cancer care is on initial diagnosis and treatment, and end of life care. The Multinational Association of Supportive Care in Cancer defines supportive care as 'the prevention and management of the adverse effects of cancer and its treatment'. This encompasses the entire cancer journey, and necessitates involvement and integration of most clinical specialties. Optimal supportive care can assist in accurate diagnosis and management, and ultimately improve outcomes. A national strategy to implement supportive care is needed to acknowledge evolving oncology practice, changing disease patterns and the changing patient demographic.